2005
DOI: 10.1176/appi.ajp.162.2.297
|View full text |Cite
|
Sign up to set email alerts
|

Suicide After Deliberate Self-Harm: A 4-Year Cohort Study

Abstract: The results highlight the importance in a suicide prevention strategy of early intervention after an episode of self-harm. Treatment should include attention to physical illness, alcohol problems, and living circumstances. Self-harm appears to confer a particularly high risk of suicide in female patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
408
2
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(449 citation statements)
references
References 22 publications
28
408
2
11
Order By: Relevance
“…De hecho, los intentos de suicidio no se incluyen en las estadísticas oficiales, cuando cada vez existen más datos sobre su importancia como factores de riesgo [8][9][10][11][12][13][14] . Harris y Barraclough 15 realizaron un meta-análisis de los estudios de seguimiento de la mortalidad, estimando que quienes intentaron suicidarse tenían una probabilidad de 38 (quienes lo intentaron empleando cualquier método) a 40 (quienes lo intentaron por envenenamiento) veces mayor de cometer suicidio que quienes no presentaron ningún intento.…”
unclassified
“…De hecho, los intentos de suicidio no se incluyen en las estadísticas oficiales, cuando cada vez existen más datos sobre su importancia como factores de riesgo [8][9][10][11][12][13][14] . Harris y Barraclough 15 realizaron un meta-análisis de los estudios de seguimiento de la mortalidad, estimando que quienes intentaron suicidarse tenían una probabilidad de 38 (quienes lo intentaron empleando cualquier método) a 40 (quienes lo intentaron por envenenamiento) veces mayor de cometer suicidio que quienes no presentaron ningún intento.…”
unclassified
“…Bongar et al suggested that 80% of patients who were admitted to emergency psychiatric services because of persistent thoughts of suicide had NSSIB (26). Cooper et al and Hawton et al concluded that, in the first 12 months after self-harm, the risk of suicide was 30 or 49 times greater than the average, respectively (27,28). In three different studies, Kimbrel et al suggested that NSSIB was a robust predictor of suicidal ideation and suicide attempts in veterans with PTSD (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…The present study is not large enough to have examined rare lethal events and they have been amalgamated here with a range of non-cutting injuries, many of which are not physically severe. Whether self-cutting is a risk for later suicide is not wholly clear in the literature, although there are recent UK studies that point to such a risk (Cooper et al, 2005;Bergen et al, 2012a;Bergen et al, 2012b). Inconsistent findings concerning suicide after self-cutting may well be tied up with sampling differences (Bergen et al, 2012a), with some follow-up cohorts based on hospital-admitted rather than ED cases, with cutting much less likely than is poisoning, or injuries other than cutting, to have led to admission (Christiansen and Jensen, 2007;Runeson et al, 2010).…”
Section: Self-injury and Suicidementioning
confidence: 99%
“…It is, however, a consistent observation that, compared with those who have attended hospital because of self-poisoning, people who attend due to self-injury are much less likely to receive adequate psychosocial assessment and ensuing aftercare. One reason for this state of affairs is almost certainly the widespread but erroneous belief that self-injury is not a suicide risk (Grandclerc et al, 2016) self-injury is, in fact, associated with higher rates of subsequent non-fatal and fatal repetition of self-harm Cooper et al, 2005;Lilley et al, 2008;Bergen et al, 2012a;Hawton et al, 2012;Carroll et al, 2014). …”
mentioning
confidence: 99%